KARAKTERISTIK KONSELI DAN PERMASALAHANNYA DALAM BIMBINGAN KONSELING - Riem Malini Pane (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan dan Bahasa Arab, 2018)
Implementation guidance and counseling there are some components that must exist to run properly and effectively. Components are a counselor, a client and issues. The counselor is the person who provided assistance while clients are those who need assistance and problems experienced by the client state; unsettling, disturbing and confusing. The problem is a challenge to counselor o develop knowledge with existing theories. The counselor is expected to assist clients out of its problems so that the client can work as usual without any problems and obstacles.